Knowledge, attitudes and practices of occupational risks in Colombian taxi drivers. Issue 1 (2nd January 2016) - Rodríguez Amaya, Reynaldo Mauricio; Becerra Pinto, Sandra Milena
Abstract : Objective . The objective of this study was to learn about the health and safety strategies in a sample of taxi drivers in Bucaramanga, Colombia. Methods . A cross-sectional study was conducted among 138 taxi drivers. A survey was used to identify the socio-demographic and working characteristics, knowledge, attitudes and practices according to their occupational risk. Results . Eighty-five percent of the workers labored 9–15 h/day. Of those who suffered accidents, 27% were not affiliated to an occupational risk administrator ( p = 0.028). Of the workers who had a work-related accident, 58% considered that the use of a cell phone while driving would not always reduce their attention, 50% always used their seat belt and 7% took active breaks and wore their seat belt ( p = 0.01). Conclusions . Within this group of taxi drivers, having or believing to possess knowledge regarding an occupational risk did not ensure that they had a safe attitude or safe working practices.